Photo album, architectural elements, Europe, circa 1900 [excerpt] (1900)
Man seated by engraved structural element. The architectural element features engraved designs, and seems to have been removed from a large portion of a wall. There are cracks and large chunks of rock missing from the top of the architectural element. The man seated next to it is wearing a suit.